4x + 4 = 2x - 6

In this equation you must combine the like terms and then solve for x. First you must use inverse operations (the opposite) to move the x's and numbers to the same sides:

Subtract 2x from 2x and move it to the side of the...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

4x + 4 = 2x - 6

In this equation you must combine the like terms and then solve for x. First you must use inverse operations (the opposite) to move the x's and numbers to the same sides:

Subtract 2x from 2x and move it to the side of the equation with 4x + 4

4x + 4 + 2x - 2x -6

4x - 2x + 4 = -6 (What you do to one side you must do to the other side - subtract 2x from 4x)

2x + 4 = -6 (Now we must move the 4 to the other side of the equation)

2x + 4 - 4 = -6 - 4

2x = -10

Then we divide both sides by 2

x = -5

4x+4 = 2x-6

4x-2x=-6-4

2x=-10

x=-5